Optogenetic regulation of endogenous gene transcription in mammals - E. S. Omelina; A. V. Pindyurin (Вавиловский журнал генетики и селекции)
Despite the rapid development of approaches aimed to precisely control transcription of exogenous genes in time and space, design of systems providing similar tight regulation of endogenous gene expression is much more challenging. However, finding ways to control the activity of endogenous genes is absolutely necessary for further progress in safe and effective gene therapies and regenerative medicine. In addition, such systems are of particular interest for genetics, molecular and cell biology. An ideal system should ensure tunable and reversible spatio-temporal control over transcriptional activity of a gene of interest. Although there are drug-inducible systems for transcriptional regulation of endogenous genes, optogenetic approaches seem to be the most promising for the gene therapy applications, as they are noninvasive and do not exhibit toxicity in comparison with druginducible systems. Moreover, they are not dependent on chemical inducer diffusion rate or pharmacokinetics and exhibit fast activation-deactivation switching. Among optogenetic tools, long-wavelength light-controlled systems are more preferable for use in mammalian tissues in comparison with tools utilizing shorter wavelengths, since far-red/near-infrared light has the maximum penetration depth due to lower light scattering caused by lipids and reduced tissue autofluorescence at wavelengths above 700 nm. Here, we review such light-inducible systems, which are based on synthetic factors that can be targeted to any desired DNA sequence and provide activation or repression of a gene of interest. The factors include zinc finger proteins, transcription activator-like effectors (TALEs), and the CRISPR/Cas9 technology. We also discuss the advantages and disadvantages of these DNA targeting tools in the context of the light-inducible gene regulation systems.